The study of the stability of aqueous three-phase fire-resistant foam in typical liquidus hydrocarbons. Issue 8 (3rd August 2019) - Fu, Gang; Jiang, Juncheng; Wei, Dan; Ni, Lei; Dou, Zhan; Chen, Qiang; Cheng, Zhen
Abstract: The utilization of solid particles in aqueous foam has a great potential in improving fire fighting efficiency. In this study, aqueous foam supported by micro fly-ash (FA) was prepared and its stability in a specific type of oil was characterized. Firstly, different amount of FA was added to study the influence of FA concentration on foamability. It showed that within a specific extent, foam expansion ratio increased with the increasing of FA concentration. And compared with conventional foams, oil resistance of FA stabilized foams, which was investigated by analyzing drainage rate and evolution process with a self-made apparatus, was remarkably improved when FA concentration exceed 4.8wt.%. Secondly, SiO2 and Al2 O3 particles with different median sizes were used to study the effect of particle size on stability. However, the smaller hydrophilic particles didn't behave better as expected. Moreover, the foam stability in three hydrocarbons was evaluated in the same way. The results indicated that the short chain hydrocarbons had much stronger detrimental effect to both two-phase foam and three-phase foam. But overall, the three-phase foam stabilized by FA exhibited much better oil resistance, so it can be used as a promising material for pool fire extinguishing and prevention.GRAPHICAL ABSTRACT